Prevalence of vulvovaginite in women rural (Research, Society and Development, 2022)
Vulvovaginitis is the most common cause of vaginal discharge in women, and the main associated consequences are: infertility, premature birth or low birth weight, miscarriage, post-cesarean endometritis, increased risk of contracting sexually transmitted diseases, such as AIDS, gonorrhea, trichomoniasis, among others. In this context, the objective of this study was to identify the prevalence of vulvovaginitis in women farmers treated at a Basic Health Unit (BHU) from the rural area of the interior of Maranhão. For this, a retrospective, cross-sectional and descriptive study was carried out with women who sought care at a UBS during the period from September 2019 to August 2020. According to the data collected, women over 51 years old predominated (28.57%), farm workers (61%), who complained of leucorrhoea, and presented: Gardnerella, Candida and HPV in the test results. The data presented in this work demonstrate how health education for women, especially for those who have low access to health services, is mandatory. This will allow the search for gynecological care to occur early, since some of the causative agents of vulvovaginitis, such as HPV, are associated with various types of cancers